A Study on The Level of Knowledge Among Dentistry Students on Infection Control Methods in Dental Colleges in Iraq: Sebuah Studi tentang Tingkat Pengetahuan Mahasiswa Kedokteran Gigi tentang Metode Pengendalian Infeksi di Perguruan Tinggi Kedokteran Gigi di Irak - Jwaid, Maher M.; Abdulhussein, Zaid A.; Teterin, Artem (Academia Open, 2024)
<div class="min-h-8 text-message flex w-full flex-col items-end gap-2 whitespace-normal break-words text-start [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="c214a994-11b3-4602-92de-5016855cced9" data-message-model-slug="gpt-4o"> Infection control is essential in dentistry to ensure patient and practitioner safety. However, gaps often exist between theoretical knowledge and practical implementation. This study assessed the knowledge, attitudes, and practices of senior dentistry students regarding infection control methods, focusing on critical areas such as handling dental chairs, sterilization processes, use of personal protective equipment, and tool storage. A questionnaire was administered to 666 participants, comprising first- to fifth-year dental students and newly graduated dentists from various academic institutions in Iraq. Results revealed that while 61.1% of respondents demonstrated adequate theoretical knowledge of sterilization procedures, adherence to best practices was inconsistent. For instance, only 10.2% of participants consistently wore protective eyewear, and 18.2% left dropped instruments unattended during procedures. Disparities in responses were statistically significant (p > 0.05), highlighting knowledge gaps in the practical application of infection control protocols. This study's findings underscore the need for systematic interventions to bridge the gap between knowledge and practice, emphasizing the role of regular seminars, practical workshops, and curriculum revisions to reinforce infection control adherence. The study provides novel insights into the critical yet underexplored area of infection control practices among dentistry students in developing countries, highlighting institutional and behavioral factors influencing compliance. These findings have broad implications for improving infection control training programs and promoting safety standards in dental education and practice. Highlights: Assess dental students' infection control knowledge, attitudes, practices. Questionnaire for preclinical and clinical students; 666 participants analyzed. High knowledge, poor adherence; recommends annual seminars to improve compliance. Keywords: dental students, infection prevention, and sterilization methods